Pengaruh Jalur Transmisi Kebijakan Moneter terhadap Inflasi di Indonesia - Fitriyani, Eka; Iranto, Dicky; Dianta, Karuniana (www.bsi.ac.id, 2023)
Historically, actual inflation could not reach the inflation target, resulting in a deviation between the actual inflation and the inflation target. To overcome this problem, Bank Indonesia implemented a monetary policy transmission channel for inflation in Indonesia through the loan interest rate channel, the exchange rate channel, and the consumption credit channel. This article aims to determine the effect of the monetary policy transmission channel on inflation in Indonesia, as seen from the interest rate, exchange rate, and consumption credit channels. The research method of this article is quantitative with VAR/VECM analysis techniques. The results of the study state that (1) in the short term, interest rates on loans and consumption credit have a significant effect on the inflation rate; (2) in the long run, loan interest rates and the rupiah exchange rate have a significant effect on the inflation rate; (3) when shocks occur in loan interest rates, the rupiah exchange rate, and consumer credit, the inflation rate will respond differently; and (4) changes in interest rates on loans and consumption credit are effective in explaining variations in changes in the inflation rate. The results of this study imply that the determination of lending rates by each bank must still refer to the reference interest rate (BI7DRR), public sentiment and the volatility of the rupiah exchange rate in the short term must be the focus of consideration in the exchange rate channel, and consumption must consider the feasibility of the 5C aspect. Keywords: Inflation, Loan Interest Rates, Rupiah Exchange Rates, Consumption Credit